Anti‐epidermal growth factor receptor monoclonal antibody plus palliative chemotherapy as a first‐line treatment for recurrent or metastatic nasopharyngeal carcinoma. (19th January 2020) - Chen, Chen; Zhou, Yixin; Zhang, Xuanye; Fu, Sha; Lin, Zuan; Fang, Wenfeng; Yang, Yunpeng; Huang, Yan; Zhao, Hongyun; Hong, Shaodong; Zhang, Li
Abstract: Background: Platinum‐based chemotherapy is the standard of care as first‐line treatment for recurrent or metastatic nasopharyngeal carcinoma (RM‐NPC); however, the prognosis of patients with RM‐NPC remains poor. The aim of this study was to evaluate the role of anti‐epidermal growth factor receptor (anti‐EGFR) antibody plus chemotherapy for RM‐NPC. Methods: RM‐NPC patients who received first‐line chemotherapy plus an anti‐EGFR antibody were recruited from Sun Yat‐Sen University Cancer Center between July 2007 and November 2017. Survival analyses were performed using the Kaplan‐Meier method with a log‐rank test. A Cox proportional hazards model was used for the multivariate analyses. Results: A total of 203 patients were enrolled in the present study. The median follow‐up time was 34.3 months (interquartile range: 19.7‐66.5 months). The median progression‐free survival (PFS) was 8.9 months (95% CI: 7.7‐10.0 months) and the median overall survival (OS) was 29.1 months (95% CI: 23.5‐34.6 months). The 1‐, 3‐, and 5‐year PFS and OS rates were 35.5% and 79.6%, 15.2% and 42.5%, and 11.6% and 23.6%, respectively. The objective response rate (ORR) was 67.5% and the disease control rate (DCR) was 91.1%. The multivariate analysis identified the following prognostic factors for PFS: anti‐EGFR agent ( P = .010), recurrence/metastasis sequence ( P = .016), KPS ( P = .017), and combined chemotherapy regimen ( P = .015). Independent risk factors for OS included age >43 years ( P = .002), Karnofsky performance score ≤80 ( P < .001), and higher level of baseline Epstein‐Barr virus (EBV) DNA ( P = .008). Leukopenia was the most common adverse event (AE) in this cohort (any grade, 84.2%; grades 3‐4, 43.4%). Conclusions: Anti‐EGFR antibody plus chemotherapy achieved promising antitumor activity with a tolerable toxicity profile in RM‐NPC. Thus, randomized clinical trials are warranted to compare the efficacy of chemotherapy with or without anti‐EGFR antibody in these patients. Abstract : Anti‐EGFR monoclonal antibody plus chemotherapy achieved promising response rate, progression‐free survival, and overall survival with a tolerable toxicity profile for recurrent or metastatic nasopharyngeal carcinoma.